5n+1=4n-2/3

Simple and best practice solution for 5n+1=4n-2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n+1=4n-2/3 equation:



5n+1=4n-2/3
We move all terms to the left:
5n+1-(4n-2/3)=0
We add all the numbers together, and all the variables
5n-(+4n-2/3)+1=0
We get rid of parentheses
5n-4n+1+2/3=0
We multiply all the terms by the denominator
5n*3-4n*3+2+1*3=0
We add all the numbers together, and all the variables
5n*3-4n*3+5=0
Wy multiply elements
15n-12n+5=0
We add all the numbers together, and all the variables
3n+5=0
We move all terms containing n to the left, all other terms to the right
3n=-5
n=-5/3
n=-1+2/3

See similar equations:

| 3/7=x1.4 | | X2+y2+2y+1=0 | | 2(5-m)+22=2(2m-7)-20 | | 2y^2+12y=-16 | | 7c-16=c+14 | | 8s+7=-33 | | 17x+2=x | | 2x.358=-2000 | | −27=6x+9 | | 2x+5=12# | | –1+a/2=15 | | 5/6=1/3c | | -9-k=-15 | | 2(4x+3)=6 | | 3x-2+7x-45=23 | | (7x+4)(5x+10)=180 | | 3y-18+2y=7y | | -11=-5c+1 | | 9+6x/7=11 | | 7(3n+1)-24n=28 | | 2(5x+4)=118 | | 2x+6x=3x+10 | | ((p+1))/(2)=4-((p+3))/(3) | | 2^n+5=36 | | 4+8x+10=30 | | 5s−3=52 | | 4p+3.5=12.5 | | 21+2t=77 | | 9x-1-7x=5-4x | | 8+3x/4=3 | | 11w=4w^2-3 | | 3y−15=3 |

Equations solver categories